P22 Do obstructive sleep apnoea (OSA) patients with normal Epworth scores comply with Continuous positive airway pressure (CPAP) therapy?. (2nd December 2011) - Pagonda, R; Thangakunam, B; Mabuto, C; Basharet, I; Yung, B; Mukherjee, D; Wadsworth, K; Samuel, J
Abstract : Introduction: Current recommendations suggest CPAP treatment in patients with OSA and excessive daytime sleepiness. The Mosaic trial showed a reduction in Epworth Sleepiness Score (ESS) in minimally symptomatic patients although there was no change in cardiovascular risk. However, patients with significant co-morbidities and objective evidence of severe OSA are often treated. The treatment compliance of patients with a normal ESS is not well established. We reviewed compliance with CPAP therapy in patients with OSA with an ESS <10 who were started on treatment due to a variety of indications. Methods: Review of CPAP compliance on the Sleep medicine database in patients diagnosed with OSA and ESS <10 from July 2008 to December 2009. Results: 86 patients with OSA and ESS <10 were started on CPAP. Indications for CPAP included daytime somnolence, morning headache, distressing apnoeic events, diabetes mellitus with complications, significant ischaemic heart disease, cerebrovascular accidents, COPD and renal failure. 33 patients (38%) had mild OSA, 33 (38%) had moderate OSA and 20 (24%) had severe OSA. The mean ESS in the mild, moderate and severe groups were 6.3, 5.4 and 5.5 respectively.27 patients (31%) were noncompliant. In this group, CPAP was withdrawn at 2 weeks in 23 patients and at 3 months in four patients. 59 patients (69%) continued to be on treatment and have had symptomatic improvement. Mean ESS in the compliant group decreased from 5.7±2.6 to 1.3±1.8 (p<0.001) post treatment. 45 (76%) of the compliant patients had an average daily CPAP usage >4 h with a mean ESS change from 5.5 to 1.1. 14 (24%) patients using CPAP <4 h found symptomatic improvement with a mean ESS change from 6.3 to 2.0. Overall in the compliant group, the mean Oxygen Desaturation Index and Apnoea Hypopnoea Index decreased by 71% and 76% respectively. Conclusion: Over two-third of patients with low ESS and symptoms/significant co-morbidities were compliant with CPAP therapy. All patients had improvement in ESS on treatment. A trial of treatment in this group of patients with a low ESS appears to be worthwhile.